2021
DOI: 10.2174/1573408017666210121114441
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Pancreatic Lipase Inhibitors from Natural Sources: A Potential Target for Obesity

Abstract: Background: Obesity is a worldwide lifestyle disorder and its incidence is growing at an alarming rate. Pancreatic lipase (PL) plays a key role in lipid metabolism and hence a potential target for obesity treatment. There have been reports that many bioactive compounds from natural sources are vast pool of PL inhibitors. Objective: In search of natural pancreatic lipase inhibitors, the review summarizes the potential of natural products for their pancreatic lipase inhibitory activity. Methods: In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, the activity was less potent than that of orlistat. Our literature review has shown that polar compounds are crucial for pancreatic lipase activity in selected plants 4,21 . And, ethanol is a polar solvent that can dissolve wide range of bioactive compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the activity was less potent than that of orlistat. Our literature review has shown that polar compounds are crucial for pancreatic lipase activity in selected plants 4,21 . And, ethanol is a polar solvent that can dissolve wide range of bioactive compounds.…”
Section: Discussionmentioning
confidence: 99%
“…There are published reports describing secondary metabolites derived from plants having lipase inhibitory activity, such as polyphenols, alkaloids, flavonoids, glycosides, saponins, terpenoids, carotenoids, and polysaccharides. As a result, safer and more efficient PL inhibitors are absolutely necessary for the treatment of obesity [4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%